Diffuse pulmonary ossification associated with fibrosing interstitial lung disease. (2019) - Alami, Badreeddine; Amara, Bouchra; Haloua, Meryem; Lmrani, Moulay Youssef Alaoui; Serraj, Mounia; Boubou, Meryem; Maaroufi, Mustapha
Abstract: Diffuse pulmonary ossification (DPO) is a rare condition that presents with metaplastic mature bone formation in the pulmonary parenchyma. DPO is usually associated with cardiovascular or respiratory disease. We report a case of 75-year-old man with chronic dyspnea, cough, asthenia and low sputum production. A chest x-ray revealed reticular pulmonary infiltrates on both sides. Computed tomography (CT) revealed peripheral, basilar predominant reticular opacities with areas of subpleural cystic change, compatible with fibrosis, fine branching calcifications within areas of linear reticulations were also visible in both mid and lower zones. Based on the clinical presentation and CT results, the patient was diagnosed with diffuse pulmonary ossification associated with idiopathic pulmonary fibrosis. Despite its rarity, the radiologist must know suggest the diagnosis of DPO especially in the presence of idiopathic pulmonary fibrosis associated with linear branched calcified densities in areas of fibrosis, avoiding a surgical biopsy that is not stripped of risk.